Intelligenza Artificiale e Agenti: sfide e opportunità etiche - Costantini, Stefania (Filosofia Morale/Moral Philosophy, 2025)
Artificial Intelligence (AI) is now a constant presence in our daily lives. From home automation to social networks, from navigation systems to healthcare, AI-powered technologies are transforming the way we live, work, and interact. But like any powerful tool, AI brings with it opportunities and risks. In this article, we will briefly review the history and main developments of AI, first of all Intelligent Agents, explore the main areas in which AI is making a difference, including healthcare, and discuss the pitfalls to avoid and the crucial role of awareness in the use of intelligent technologies.